Effect of gamma irradiation and storage time on microbial growth and physicochemical characteristics of pumpkin (Cucurbita Moschata Duchesne ex Poiret) puree - Gliemmo, María Fernanda (2013)
The effect of gamma irradiation (0–2 kGy) and storage time (0–28 days) on microbial growth and physicochemical characteristics of a packed pumpkin puree was studied. For that purpose, a factorial design was applied. The puree contained potassium sorbate, glucose and vanillin was stored at 25 ℃. Gamma irradiation diminished and storage time increased microbial growth. A synergistic effect between both variables on microbial growth was observed. Storage time decreased pH and color of purees. Sorbate content decreased with storage time and gamma irradiation. Mathematical models of microbial growth generated by the factorial design allowed estimating that a puree absorbing 1.63 kGy would have a shelf-life of 4 days. In order to improve this time, some changes in the applied hurdles were assayed. These included a thermal treatment before irradiation, a reduction of irradiation dose to 0.75 kGy and a decrease in storage temperature at 20 ℃. As a result, the shelf-life of purees increased to 28 days.